(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article there is an analysis of approaches to judgement of inter-generational mutual relations between children and parents. Cardinal changes in social and economic, political and cultural relations have caused essential changes in social and cultural continuity of generations.